What is your first step in solving this equation? 4(3x−2)=−24
5 answers
The first step in solving this equation is to distribute the 4 to the terms inside the parentheses.
can you show the steps
Certainly! Here are the steps to solve the equation 4(3x-2) = -24:
1. Distribute the 4 to the terms inside the parentheses:
4 * 3x - 4 * 2 = -24
12x - 8 = -24
2. Simplify the equation by combining like terms:
12x - 8 = -24
3. Move the constant term to the other side of the equation by adding 8 to both sides:
12x - 8 + 8 = -24 + 8
12x = -16
Hence, the first step is to distribute the 4 to the terms inside the parentheses, which gives us the equation 12x - 8 = -24.
1. Distribute the 4 to the terms inside the parentheses:
4 * 3x - 4 * 2 = -24
12x - 8 = -24
2. Simplify the equation by combining like terms:
12x - 8 = -24
3. Move the constant term to the other side of the equation by adding 8 to both sides:
12x - 8 + 8 = -24 + 8
12x = -16
Hence, the first step is to distribute the 4 to the terms inside the parentheses, which gives us the equation 12x - 8 = -24.
can you isolate it please
Apologies for missing the isolation step. Let's continue from where we left off:
4. To isolate the variable x, we need to get rid of the constant term on the left side of the equation. We can do this by adding 8 to both sides of the equation:
12x - 8 + 8 = -16 + 8
Simplifying the equation further:
12x = -8
5. Finally, to solve for x, divide both sides of the equation by 12:
(12x)/12 = -8/12
Simplifying the equation further:
x = -2/3
Therefore, the solution to the equation 4(3x-2) = -24 is x = -2/3.
4. To isolate the variable x, we need to get rid of the constant term on the left side of the equation. We can do this by adding 8 to both sides of the equation:
12x - 8 + 8 = -16 + 8
Simplifying the equation further:
12x = -8
5. Finally, to solve for x, divide both sides of the equation by 12:
(12x)/12 = -8/12
Simplifying the equation further:
x = -2/3
Therefore, the solution to the equation 4(3x-2) = -24 is x = -2/3.